Shallow methane hydrate system controls ongoing, downslope sediment transport in a low‐velocity active submarine landslide complex, Hikurangi Margin, New Zealand. (7th November 2014) - Mountjoy, Joshu J.; Pecher, Ingo; Henrys, Stuart; Crutchley, Gareth; Barnes, Philip M.; Plaza‐Faverola, Andreia
Abstract Morphological and seismic data from a submarine landslide complex east of New Zealand indicate flow‐like deformation within gas hydrate‐bearing sediment. This "creeping" deformation occurs immediately downslope of where the base of gas hydrate stability reaches the seafloor, suggesting involvement of gas hydrates. We present evidence that, contrary to conventional views, gas hydrates can directly destabilize the seafloor. Three mechanisms could explain how the shallow gas hydrate system could control these landslides. (1) Gas hydrate dissociation could result in excess pore pressure within the upper reaches of the landslide. (2) Overpressure below low‐permeability gas hydrate‐bearing sediments could cause hydrofracturing in the gas hydrate zone valving excess pore pressure into the landslide body. (3) Gas hydrate‐bearing sediment could exhibit time‐dependent plastic deformation enabling glacial‐style deformation. We favor the final hypothesis that the landslides are actually creeping seafloor glaciers. The viability of rheologically controlled deformation of a hydrate sediment mix is supported by recent laboratory observations of time‐dependent deformation behavior of gas hydrate‐bearing sands. The controlling hydrate is likely to be strongly dependent on formation controls and intersediment hydrate morphology. Our results constitute a paradigm shift for evaluating the effect of gas hydrates on seafloor strength which, given the widespread occurrence of gas hydrates in the submarine environment, may require a reevaluation of slope stability following future climate‐forced variation in bottom‐water temperature.